2019
DOI: 10.1128/jvi.01488-18
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between ORF18 and ORF30 Is Required for Late Gene Expression in Kaposi's Sarcoma-Associated Herpesvirus

Abstract: In the beta- and gammaherpesviruses, a specialized complex of viral transcriptional activators (vTAs) coordinate to direct expression of virus-encoded late genes, which are critical for viral assembly and whose transcription initiates only after the onset of viral DNA replication. The vTAs in Kaposi’s sarcoma-associated herpesvirus (KSHV) are ORF18, ORF24, ORF30, ORF31, ORF34, and ORF66. While the general organization of the vTA complex has been mapped, the individual roles of these proteins and how they coord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 31 publications
8
38
0
Order By: Relevance
“…Interaction of ORF66 and ORF34 and its function in virus production. ORF66 was reported to interact with other vPIC components, such as ORF31, ORF18, and ORF34, by us and others (17,19,21). We also found that ORF34 operated as the vPIC hub, by bridging ORF24 and vPIC components, including ORF66.…”
Section: P=103 X 10 -7supporting
confidence: 70%
“…Interaction of ORF66 and ORF34 and its function in virus production. ORF66 was reported to interact with other vPIC components, such as ORF31, ORF18, and ORF34, by us and others (17,19,21). We also found that ORF34 operated as the vPIC hub, by bridging ORF24 and vPIC components, including ORF66.…”
Section: P=103 X 10 -7supporting
confidence: 70%
“…We assessed the ability of the NTD chimeras to functionally complement ORF24 using an established transfection-based late gene transcription assay [13][14][15]. The six vTAs (ORFs 18, 30, 31, 34, 66 and either WT ORF24, its homologs, or chimeras) were co-transfected into HEK293T cells, along with a firefly luciferase reporter controlled by the K8.1 late gene promoter or, as a control, the early ORF57 promoter.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…First, β/γ late gene transcription is regulated in part by a core promoter sequence 12-15 base pairs in length that has a TATT motif followed by a RVNYS motif in lieu of the canonical TATA box found in early viral promoters and in some cellular promoters [8][9][10][11]. Additionally, late gene expression requires at least six viral proteins, called viral transcriptional activators (vTAs), which form a complex at late gene promoters [12][13][14][15][16][17]. Little is known about the functional role these vTAs play in late gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the paucity of functional information on the individual vPIC components, protein-protein interaction mapping has provided insight into the overall complex organization [13,18]. Furthermore, point mutants that disrupt individual inter-subunit vPIC interactions abrogate late gene transcription, highlighting the fact that vPIC complex integrity is critical for function [13,20,21].…”
Section: Introductionmentioning
confidence: 99%